Overcoming Inequalities in the Labor Market: Can Educational Measures Strengthen the Agency and Resilience of Migrants, Refugees, and their Descendants? - (:unkn) unknown (My University, 2025)
This project enhances our understanding of the continued labor market disadvantage of young immigrants, refugees, and their descendants by examining processes leading to ethnic disadvantage in the labor market. We examine the conditions under which immigrants gain agency and move from being objects of discrimination and inequalities related to education and the labor market to successfully completing formal education and getting a job. We combine theories on cumulative discrimination and resilience. Protective factors on ethnic disadvantage that facilitate advancement in one life domain also facilitate advancement in others (e.g., labor market, formal education). We examine how disadvantaged immigrants and refugees maneuver within structures, and ask the following research questions: How can educational measures strengthen the agency and resilience of migrants, refugees, and their descendants with regard to labor-market outcomes and hiring decisions? How does increased geographical mobility affect individual educational outcomes and hiring decisions? How do immigrants signal resilience in the face of anticipated discrimination in the labor market? Which are the empirically validated individual and societal resilience pathways in education linked to overcoming discrimination in the labor market? The project is focusing on young immigrants, refugees, and children of labor migrants as some of the most disadvantaged groups in contemporary Western labor markets.
Keywords: discrimination; migration